Connections and Capacity: An Exploration of Preservice Teachers' Sense of Belonging, Social Networks, and Self-Efficacy in Three Teacher Education Programs - Peter Bjorklund; Alan J. Daly; Rebecca Ambrose; Elizabeth A. van Es (SAGE Publishing, 2020)
Learning to teach is rife with challenges. Preservice teachers' self-efficacy can potentially mitigate the stress of these challenges, and teacher education programs are fundamental in helping them build this important resource. As such, understanding the foundations of self-efficacy is important for researchers and teacher educators alike. Grounding our study in social network theory, we explored the relationship between sense of belonging to a teacher education program, network centrality, and self-efficacy. Our sample included 245 preservice teachers in three university teacher education programs. We found that sense of belonging to the program and network centrality (in-degree and out-degree) were significantly and positively related to preservice teachers' self-efficacy beliefs. This study builds on a growing literature that explores the relationships between preservice teachers' social networks and their beliefs and practices.